EU enlargement and Finnish forestry industry: A special emphasis on the packaging industry - Colin Hazley (The Research Institute of the Finnish Economy (ETLA), 2001)
The aim of the project was to provide an overview of the competitiveness of the forest-based and related industries in the 10 CEECs, from the Finnish point of view, and to study in particular the development potential for the Finnish packaging industry in the region. An important question is what effect will Eastern expansion have at the industry sector level, and how will this translate to various EU regions, and in particular, Finland. In Part I of this report, the relative cost advantage of countries in central and eastern Europe is demonstrated. In Part II, the potential for the Finnish forest industry in these countries is explored in more detail. Developments in central and eastern Europe will alter the landscape in terms of the location of production facilities in some key areas for the Finnish forest industry. It was shown that most of the potential for the Finnish forest industry in central and eastern Europe appeared to exist for the pulp and paper industry. One of the most profound changes, which will indirectly affect the future of the Finnish fibre-based packaging sector, is that of the shift in the manufacturing base of various sectors of industry to lower cost producing countries of the CEEC region. – – Projektin tarkoituksena oli tarkastella metsäperustaisen teollisuuden ja sen liitännäistoimialojen kilpailukykyä Suomen näkökulmasta kymmenessä Keski- ja Itä- Euroopan maassa (KIE-maat). Tutkimuksessa tarkastellaan erityisesti suomalaisen pakkaustuoteteollisuuden kehitysmahdollisuuksia alueella. Keskeinen kysymys on, mitkä ovat EU:n itälaajentumisen toimialatason vaikutukset, ja mitä ne merkitsevät EU:n eri alueiden ja erityisesti Suomen kannalta. Raportin ensimmäisessä osassa tarkastellaan Keski- ja Itä-Euroopan maiden suhteellista kustannusetua. Raportin toisessa osassa tarkastellaan yksityiskohtaisemmin näiden maiden suomalaiselle metsäteollisuudelle tarjoamia mahdollisuuksia. Keski- ja Itä-Euroopassa tapahtuva kehitys tulee muuttamaan yritystoiminnan kenttää vaikuttaen tuotantolaitosten sijoittumiseen joillain suomalaisen metsäteollisuuden avainalueilla. Tarkastelun perusteella eniten mahdollisuuksia suomalaiselle metsäteollisuudelle Keski- ja Itä-Euroopassa näyttää olevan sellu- ja paperiteollisuudessa. Yksi perustavanlaatuisista muutoksista, joka tulee epäsuorasti vaikuttamaan suomalaisen kuitupohjaisen pakkaustuotealan tulevaisuuteen, on eri teollisuusalojen tuotantopohjan siirtyminen matalamman tuotantokustannustason maihin Keski- ja Itä-Euroopassa.
Keywords: 330; Finnish forest industry; competitiveness; CEEC countries; EU enlargement; Suomen metsäteollisuus; kilpailukyky; KIE-maat; itälaajentuminen; EU-Erweiterung; Forstwirtschaft; Verpackungsindustrie; Ostmitteleuropa; Finnland